Added value of diffusion‐weighted images and dynamic contrast enhancement in multiparametric magnetic resonance imaging for the detection of clinically significant prostate cancer in the PICTURE trial. (11th December 2019) - Eldred‐Evans, David; Neves, Joana B.; Simmons, Lucy A.M.; Kanthabalan, Abi; McCartan, Neil; Shah, Taimur T.; Arya, Manit; Charman, Susan C.; Freeman, Alex; Moore, Caroline M.; Punwani, Shonit; Emberton, Mark; et al.
Abstract : Objective: To determine the additional diagnostic value of diffusion‐weighted imaging (DWI) and dynamic contrast‐enhanced imaging (DCE) in men requiring a repeat biopsy within the PICTURE study. Patients and Methods: PICTURE was a paired‐cohort confirmatory study in which 249 men who required further risk stratification after a previous non‐magnetic resonance imaging (MRI)‐guided transrectal ultrasonography‐guided biopsy underwent a 3‐Tesla (3T) multiparametic (mp)MRI consisting of T2‐weighted imaging (T2W), DWI and DCE, followed by transperineal template prostate mapping biopsy. Each mpMRI was reported using a LIKERT score in a sequential blinded manner to generate scores for T2W, T2W+DWI and T2W+DWI+DCE. Area under the receiver‐operating characteristic curve (AUROC) analysis was performed to compare the diagnostic accuracy of each combination. The threshold for a positive mpMRI was set at a LIKERT score ≥3. Clinically significant prostate cancer was analysed across a range of definitions including UCL/Ahmed definition 1 (primary definition), UCL/Ahmed definition 2, any Gleason ≥3 + 4 and any Gleason ≥4 + 3. Results: Of 249 men, sequential MRI reporting was available for 246. There was a higher rate of equivocal lesions (44.6%) using T2W alone compared to the addition of DWI (23.9%) and DCE (19.8%). Using the primary definition of clinically significant disease, there was no significant difference in the overall accuracy between T2W, with an AUROC of 0.74 (95% confidence interval [CI] 0.68–0.80), T2W+DWI at 0.76 (95% CI 0.71–0.82), and T2W+DWI+DCE, with an AUROC of 0.77 (95% CI 0.71–0.82; P = 0.55). The AUROC values remained comparable using other definitions of clinically significant disease including UCL/Ahmed definition 2 ( P = 0.79), Gleason ≥3 + 4 ( P = 0.53) and Gleason ≥4 + 3 ( P = 0.53). Conclusions: Using 3T MRI, a high level of diagnostic accuracy can be achieved using T2W as a single parameter in men with a prior biopsy; however, such a strategy can lead to a higher rate of equivocal lesions.